Pandau Jaya Waste Bank Socialization In Kampar Regency, Riau Province - Nurhayani Lubis; Hardi Hardi; Nofrizal Nofrizal (Institut Riset dan Publikasi Indonesia, 2021)
The purpose of this activity is to provide an understanding of the benefits of waste banks to the community. This is done because there are still many people who do not know about the waste bank. The initial motivation in establishing the Pandau Jaya Waste Bank was to support the Kampar Regency government program in managing waste that had been issued by the Kampar Regency Regent through Perbup No 40 of 2018. In addition, it was also to provide education about the economic value of waste. Namely that waste can also be an additional side income for the surrounding community. However, due to lack of information and understanding, Pandau Jaya Waste Bank does not yet have a place in the community. Therefore, it is necessary to socialize the Pandau Jaya Waste Bank which contains education about the economic value of waste to the community in the RW where the waste bank is established. The methods used in this service are lectures, distribution of questionnaires before and after socialization, and discussions. The lecture was directly filled by Mr. Prama Widayat as the owner of the Pandau Jaya Waste Bank. Attended by the heads of RT and RW throughout Pandau Jaya Village, this service went smoothly, several RT and RW heads gave their appreciation by visiting the Pandau Jaya Waste Bank directly to see the work process at the Waste Bank.